MYC Immunohistochemistry Predicts MYC Rearrangements by FISH - Nwanze, Julum; Siddiqui, Momin T.; Stevens, Keith A.; Saxe, Debra; Cohen, Cynthia (Frontiers in Oncology, 2017)
MYC is the proto-oncogene classically associated with Burkitt lymphoma (BL) located at chromosomal locus 8q24. Rearrangements of MYC are seen in nearly 100% of BL, but have been reported in 3-16% of Diffuse Large B-cell Lymphomas (DLBCL). Rearrangements of MYC are tested for by fluorescent in-situ hybridization (FISH). In this study, we compared immunohistochemistry (IHC) using a monoclonal antibody directed against the human Myc protein to the current method, FISH. 31 cases were identified that had been tested for MYC rearrangements by FISH over 27 months with heterogeneity in the diagnoses: 5 BL; 10 DLBCL; 3 B-cell lymphoma unclassifiable between DLBCL and BL; 5 B-cell lymphoma not otherwise specified (NOS); 1 EBV-related B-cell lymphoma; 1 composite CLL/SLL-large cell lymphoma, and 6 designated as high-grade or aggressive B-cell lymphoma. Analysis by FISH was performed as part of the clinical work-up, where a MYC rearrangement is defined as a split fusion signal in at least 5.7% of cells. . Myc-IHC was interpreted as a qualitative positive (overexpressed) or negative (not overexpressed) result. 12 cases (39%) were positive for MYC rearrangements by FISH. Overall, 13 cases (42%) showed Myc overexpression by IHC, 11 of which harbored a MYC rearrangement by FISH. There were two false positives and one false negative. Thus, Myc-IHC predicted a MYC-rearrangement by FISH with 92% sensitivity and 89% specificity. We can thus conclude that Myc-IHC should be a potentially useful screening tool for identifying lymphomas that may harbor a MYC-rearrangement. Keywords: MYC, immunohistochemistry, Burkitt lymphoma, in situ hybridization, MYC rearrangement